(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The study of agricultural GDP, whether at the macro level or at the sectoral level, is important when carrying out studies and research related to macroeconomics, as it gives the researcher a good idea of the reality of the economy for all or within the agricultural sector targeted by the study, and the problem of searching for the continuous decline of agricultural GDP from GDP, which leads to a decline and decline of the agricultural sector and its development in the wrong direction targeted by economic policies and comprehensive development plans. From here, the research aimed to study the factors affecting agricultural GDP in Iraq and time series data were collected for the period (1990-2022) for the variables included in the model. The ARDL model was used to analyze the data and to identify the factors affecting agricultural GDP, including agricultural investments, agricultural labor, agricultural exports, agricultural loans and GDP, where the results showed an inverse relationship between agricultural GDP, agricultural labor and agricultural exports. It was also found that there is a positive relationship between Agricultural GDP, agricultural investments, agricultural loans and GDP, the research recommended facilitating the procedure for obtaining agricultural loans and the use of policies related to agricultural investments to reflect on the agricultural GDP and encourage the private sector to expand and promote agricultural investments in the agricultural sector.